Parenting practices during early childhood: validity evidence of a Brazilian scale - Olga Maria Piazentin Rolim Rodrigues; Elisa Rachel Pisani Altafim; Veronica Aparecida Pereira; Sária Cristina Nogueira; Rafaela de Almeida Schiavo (Elsevier, 2022)
Objective: The present study aims to analyze the validity of evidence and internal consistency of an inventory for assessing parenting practices during early childhood. Method: Participants were 857 mothers of one-to-42-months children recruited in three cities in the Southeast region and one city in the Midwest region of Brazil. The participants answered a sociodemographic questionnaire with maternal and child data, and the Parenting Styles Inventory for Mothers of Babies (IEPMB). The IEPMB includes 25 questions about positive and negative parenting practices that mothers use to raise their children. An exploratory and confirmatory factor analysis was conducted using the following criteria to indicate adequate model fit: root-mean-square error of approximation (RMSEA) < .08; standardized root mean square residual (SRMR) < .09; comparative fit index (CFI) > 0.90. For the hypothesis-testing method, a comparison between groups using a student's t-test based on the child's age (infants vs. toddlers) and mother's age (adolescents vs. adults) was carried out. Results: The final 11 items model of the measure revealed an adequate overall model fit (RMSEA = 0.04; SRMR = 0.04; CFI = 0.94). The items were grouped into three constructs: Aggressiveness and Emotional Dysregulation, Relaxed Discipline, and Positive Monitoring. Adolescent mothers reported less positive monitoring than adult mothers (p < 0.001). Mothers of toddlers reported more aggressiveness/emotional dysregulation (p < 0.001) and relaxed discipline (p = 0.05) than mothers of infants. Conclusions: The instrument named from this study as the Parenting Practices Inventory for Mothers of Babies showed evidence for measuring mothers' parenting practices in early childhood and allows the identification of parents who need support.